Alleviating Al-Qur'an Illiteracy in Public Universities: A Case Study of the Al-Qur'an Reading Guidance Program at Universitas Negeri Malang: Studi Kasus Program Bimbingan Baca al-Qur’an di Universitas Negeri Malang - Siti Lailatul Isnaini; Yusuf Hanafi; Ahmad Munjin Nasih; Ibnu Samsul Huda (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2022)
The competence of reading the holy book correctly and adequately is the obligation of every religious person. Ironically, many Muslim students do not have adequate skills in reading the Qur'an. Therefore, Universitas Negeri Malang (UM) launched a campaign to be free of Qur'an illiteracy for its students. This study aims to describe the planning, implementation, evaluation, and effectiveness of Qur'an learning at UM and the correlation of Arabic language skills to the ability to read the al-Qur'an. The method used is a mixed-method with an exploratory sequential design. The quantitative data analysis technique used normality test, Wilcoxon signed ranks, d-effect size, and calculation of N-gain value. The results of the study are as follows: (1) learning planning is carried out in a centralized and detailed manner; (2) the implementation of learning adapts to class groupings, and learning steps specified in the Qur'an Reading Guidance curriculum; (3) evaluation of learning is carried out using tashih techniques, post-test, and assessment of learning attitudes; (4) learning effectiveness is in the high category, which is indicated by the d-effect size value of 0.76, and (5) Arabic language ability is found to have a significant correlation with the ability to read the Qur'an. In general, UM is considered successful in reducing the level of Qur'an illiteracy among students.